Factors associated with variation in single-dose albendazole pharmacokinetics: A systematic review and modelling analysis. - Charles Whittaker; Cédric B Chesnais; Sébastien D S Pion; Joseph Kamgno; Martin Walker; Maria-Gloria Basáñez; Michel Boussinesq (PLoS Neglected Tropical Diseases)
Background Albendazole is an orally administered anti-parasitic medication with widespread usage in a variety of both programmatic and clinical contexts. Previous work has shown that the drug's pharmacologically active metabolite, albendazole sulfoxide, is characterised by substantial inter-individual pharmacokinetic variation. This variation might have implications for the efficacy of albendazole treatment, but current understanding of the factors associated with this variation remains incomplete. Methodology/principal findings We carried out a systematic review to identify references containing temporally disaggregated data on the plasma concentration of albendazole and/or (its pharmacologically-active metabolite) albendazole sulfoxide following a single oral dose. These data were then integrated into a mathematical modelling framework to infer albendazole sulfoxide pharmacokinetic parameters and relate them to characteristics of the groups being treated. These characteristics included age, weight, sex, dosage, infection status, and whether patients had received a fatty meal prior to treatment or other drugs alongside albendazole. Our results highlight a number of factors systematically associated with albendazole sulfoxide pharmacokinetic variation including age, existing parasitic infection and receipt of a fatty meal. Age was significantly associated with variation in albendazole sulfoxide systemic availability and peak plasma concentration achieved; as well as the clearance rate (related to the half-life) after adjusting for variation in dosage due to differences in body weight between children and adults. Receipt of a fatty meal prior to treatment was associated with increased albendazole sulfoxide systemic availability (and by extension, peak plasma concentration and total albendazole sulfoxide exposure following the dose). Parasitic infection (particularly echinococcosis) was associated with altered pharmacokinetic parameters, with infected populations displaying distinct characteristics to uninfected ones. Conclusions/significance These results highlight the extensive inter-individual variation that characterises albendazole sulfoxide pharmacokinetics and provide insight into some of the factors associated with this variation.